Computational Calculation of Nitrobenzene and Its Derivatives - Maahury, Mirella Fonda; Amos, Matthew Adi Honey (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2022)
Nitrobenzene is one of benzene derivatives. Nitrobenzene can be found naturally and also from the synthesis process. Nitrobenzene is used as a raw material to synthesize aniline, textile dyes, pesticides, and drugs. Nitrobenzene is a solvent in the paint industry. The computational calculation was performed for nitrobenzene and its derivatives. Nitrobenzene and its four nitrobenzene derivatives have been optimized using density functional theory/B3LYP functional. The basis set is 3-21G(d). The optimized structure from geometry optimization of the nitrobenzene and its derivatives are in one plane (planar). The parameter structure is changed when substituents change. The bond length increases, and the bond angle decreases when substituents are present.